Isoflavones Inhibit Hydrogen Peroxide-Induced Angiotensinogen Secretion in Mesangial Cells - Masumi, Kamiyama; Mana, Ookawa; Rika, Saito; Noa, Tange; Mariyo, Hashizume; Misuzu, Matsunaga; Riko, Yokota; Ayaka, Yoshihara; Tamami, Iwamoto (Current topics in nutraceuticals research, 2024)
The mechanisms underlying increased angiotensinogen secretion in diabetic nephropathy are unknown. This study aimed to examine the mechanism of increased angiotensinogen secretion in mesangial cells. Additionally, we explored the effects of antioxidant compounds, such as isoflavones, on angiotensin secretion. Angiotensinogen expression and secretion were evaluated in mesangial cells treated with hydrogen peroxide. We investigated the effects of pretreatment with catalase, daidzein, and equol and inhibitors of mitogen-activated protein kinase, stress-stimulated kinase p38, or c-Jun NH2-terminal kinase. The 1,1-diphenyl-2-picrylhydrazyl radical scavenging assay revealed that daidzein and equol have antioxidant properties. Hydrogen peroxide stimulated angiotensinogen expression and secretion in mesangial cells in a concentrationdependent manner. Catalase, daidzein, and equol reduced the enhanced angiotensinogen expression and secretion induced by hydrogen peroxide. We examined the mitogen-activated protein kinase cascade to explore cell signaling mechanisms involved in angiotensinogen induction. We hypothesize that stress-stimulated kinase p38 and c-Jun NH2-terminal kinase were crucial in the mechanisms. We found that hydrogen peroxide enhanced angiotensinogen expression and secretion in mesangial cells. However, daidzein and equol decreased this enhancement. Increased angiotensinogen secretion will enhance stress-stimulated kinase p38 and c-Jun NH2-terminal kinase.